INCIDENCE AND RISK FACTORS OF DRUG POISONING IN CHILDREN - Begnaeva Mukhiba Usmanovna (Journal of Science in Medicine and Life, 2024)
Throughout the world, the situation of acute poisoning is steadily increasing. Due to the wide distribution of various chemical and pharmacological drugs in the environment. More and more children are admitted to toxicology departments with a diagnosis of acute poisoning. In this regard, we studied the medical histories of 280 sick children admitted to the Republican Research Center for Emergency Medicine of the Samarkand branch and determined the frequency of occurrence, causes, risk factors and developed the prevention of drug poisoning in children.